2021
DOI: 10.1364/ol.436316
|View full text |Cite
|
Sign up to set email alerts
|

Strong optomechanical coupling in chain-like waveguides of silicon nanoparticles with quasi-bound states in the continuum

Abstract: We propose and demonstrate that strong optomechanical coupling can be achieved in a chain-like waveguide consisting of silicon nanorods. By employing quasi-bound states in the continuum and mechanical resonances at a frequency around 10 GHz, the optomechanical coupling rate can be above 2 MHz and surpass most microcavities. We have also studied cases with different optical wave numbers and size parameters of silicon, and a robust coupling rate has been verified, benefiting the experimental measurements and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
2
Order By: Relevance
“…We have simulated the eigenmode of this ring resonator with the Finite Element Method (COMSOL Multiphysics), and the optical and mechanical parameters of silicon are similar to that in ref. 50. The interested optical mode at the wavelength of 1550 nm is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have simulated the eigenmode of this ring resonator with the Finite Element Method (COMSOL Multiphysics), and the optical and mechanical parameters of silicon are similar to that in ref. 50. The interested optical mode at the wavelength of 1550 nm is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[47][48][49] Recently, we have also proposed and shown that chain-like silicon waveguides can confine optical waves via the quasi-bound states in the continuum while each silicon unit acts as a mechanical resonator, thus realizing a considerable optomechanical coupling rate. 50 However, it is necessary to use a dozen nanorods to achieve the desired effect, the waveguide should be long enough, leading to a long waveguide and a footprint larger than tens of wavelengths. In addition, as a well-confined optical mode can facilitate the optomechanical interaction, the concept of bound states in the continuum is a promising platform and has been widely studied with various nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…В статье также представлены избранные результаты в области фотоники, радиофотоники и оптических 2D метаматериалов (ММ), которые были получены автором с китайскими учеными в совместной лаборатории информационных технологий и фрактальной обработки сигналов в Китае [10][11][12][13][14][15][16][17] за период 2019-2021 гг.…”
unclassified
“…Кроме того, интенсивность света на выходе из МП очень похожа на идеальную, что подразумевает высокое качество обнаружения границ для изображений с МП Лапласа.Ввиду ограниченного объема статьи автор лишь конспективно перечислит другие направления фотоники, которые также исследуются в наших работах[10][11][12][13][14][15][16][17] и подробно там представлены. Это: управление рассеянием света наночастицами с помощью магнитоэлектрической связи и нулевое обратное рассеяние (теория рассеяния света наночастицами и электромагнитные мультиполи, численное моделирование, проверочные эксперименты в области частот от 4 до 7.5 ГГц)[10,13,14]; сильная оптомеханическая связь в цепочечных волноводах из наночастиц кремния с квазисвязанными состояниями в континууме (фотон-фононное взаимодействие с микроструктурами)[17] и т.п. Эти направления, несомненно, могут стать темами будущих докладов на конференциях "Радиолокация, навигация, связь -RLNC" в ВГУ.Рис.…”
unclassified